Racism in the Chronicles of Doctor Moacyr Scliar (Global Journal of Human-Social Science, 2024)
The attention in this article falls on an expressive niche of Moacyr Scliar s literature the chronicles Expanding the proposal that the writer made use of his experiences to compose his works it is highlighted that the media and among them cinema are the target of the writer s attention they appear as a theme in his chronicles and appear in them as an intertext and intermidiatic reference It is identified that his performance as a chronicler is marked by the logic of the press with publications in newspapers and books After mapping the phases attributed to his literature there is a thematic association between medicine and cinema in his chronicles in which cinema and film works appear as a compositional resource as a motive or setting to exemplify complex issues or to illustrate reflections in a concrete way about racism
Keywords: chronicles; medicine; cinema; racism